2007
DOI: 10.21608/ejabf.2007.1951
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and biological studies on the Nile tilapia Oreochromis niloticus along different sites of lake Burullus

Abstract: ABSTRACTake Burullus represents an economically important lake in Egypt , due to its rich fishery resources. Unfortunately, the lake is exposed to many kinds of chemical and biological pollutants in addition to the remains of agricultural and wastes that are disposed into it. So, the aim of the present study was compare the quality of water samples collected from three different sites along lake Burullus; a site of the lake in contact with the Mediterranean sea called ElBoughaz inlet, western sector of the lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
9
11
0
Order By: Relevance
“…The histopathological changes observed in the liver of O. niloticus are similar to that recorded by Zaghloul et al (2007) and Abdel-Aziz et al (2011), which confirmed the present study biochemical change in the liver enzymes; AST and ALP and in agreement with Ajani and Akpoilih (2010) who found that the liver tissue necrosis was associated with the elevation of the activates of ALT and AST. The kidney is a major organ involved in fluid and ionic balance of fish.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The histopathological changes observed in the liver of O. niloticus are similar to that recorded by Zaghloul et al (2007) and Abdel-Aziz et al (2011), which confirmed the present study biochemical change in the liver enzymes; AST and ALP and in agreement with Ajani and Akpoilih (2010) who found that the liver tissue necrosis was associated with the elevation of the activates of ALT and AST. The kidney is a major organ involved in fluid and ionic balance of fish.…”
Section: Discussionsupporting
confidence: 93%
“…The present kidney pathological alterations included vacuolization, dilation in renal cells, necrosis, glomerular shrinkage and vacuolar degeneration in the epithelium of renal tubules and separation from the basement membrane resulting from edema. These symptoms are similar with that observed by Zaghloul (2000) and Zaghloul et al (2007) and similar to those found in Mugil sp. and C. carpio that exposed to lindane (Ortiz et al, 2003); O. mykiss infected with Micrococcus luteus (Aydin et al, 2005) O. niloticus exposed to ammonia (Benli et al, 2008); Dicentrarchus labrax exposed to mercury (Giari et al, 2007) and O. niloticus exposed to Cu and Pb (Osman et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations